Genes and light: many years later - A. O. Ruvinsky (Вавиловский журнал генетики и селекции, 2017)
This paper commemotates centenary anniversary of Professor D.K. Belyaev and discusses his studies of photoperiodic changes on mammalian reproduction and embryonic development in the realm of modern data. Georgian white mutation (W G) in silver-black foxes was used as a model for such investigations. Ability of W G/W G homozygotes in standard photoperiodic conditions to go successfully through the implantation process is sharply reduced. Experimental elongation of daily light period for pregnant females from W G/w × W G/w crosses led to a very significant increase of W G/W G homozygotes in the progeny. Georgian white mutation likely causes a low expression of KIT gene. Presented here considerations of KIT protein and its ligand KITLG molecular and cellular interactions suggest a possibility for slow development of W G/W G blastocysts; hence many such blastocysts might be late and miss an opportunity for successful implantation. The discussed experimental photoperiodic change might influence a number of processes including developmental acceleration of W G/W G blastocysts, slow down trophopblast outgrowth of almost mature blastocysts, promotion of endometrial readiness and possible delay of the implantation start. All these processes could create more supportive conditions for successful implantation of W G/W G blastocysts.